Comet 289P/Blanpain: Near-perihelion Activity and the Phoenicids - Toshihiro Kasuga (The Astronomical Journal)
We present NEOWISE observations of Jupiter family comet 289P/Blanpain, the parent body of the Phoenicid meteoroid stream. Near-infrared images at 3.4 μ m (W1) and 4.6 μ m (W2) were obtained near perihelion on two occasions: UT 2019 October 30 (inbound, heliocentric distance R _h = 1.20 au) and UT 2020 January 11–12 (outbound, R _h = 1.01 au). To assess faint activity, we establish constraints on dust production driven by the limited sublimating area of water ice, based on studies of the 1956 Phoenicids. The ejected dust masses are M _d = 4100 ± 200 kg (inbound) and 1700 ± 200 kg (outbound), respectively. The dust production rates are Q _dust = 0.01–0.02 kg s ^−1 , corresponding to a dust-to-gas production ratio of 2 ≤ f _dg ≤ 6. The resulting fractional active area, f _A = 3.8 ± 1.9 × 10 ^−5 , is the smallest yet reported. The absence of 4.6 μ m (W2) excess suggests that 289P/Blanpain contains negligible amounts of CO _2 and CO. Time-resolved analysis of the weighted mean of the W1 and W2 magnitudes finds a distinctive peak amplitude in the light curve having a rotational period P _rot = 8.8536 ± 0.3860 hr, however, further verification is needed. The perihelion-normalized nongravitational acceleration, ${α }_{{\rm{NG}}}^{′} $ = 3.1 × 10 ^−6 , is approximately an order of magnitude smaller than the trend observed for well-studied comets, consistent with weak outgassing. Current dust production from 289P/Blanpain, regardless of plausible assumptions for the particle size and distribution, is an order of magnitude too small to produce the Phoenicid stream within its ~300 yr dynamical lifetime. This suggests another mass supply, probably in 1743–1819, from rapid rotational destruction of a subkilometer precursor body, resulting in fragments equaling the mass of an object with radius ~ 100 m.